Efficacy and Safety of a Patient Selection Tool for Predicted Discharge at an Ambulatory Surgical Center: A Pilot Study - Salvador A. Forte, DO; Lucas Bartlett, DO; Temisan Osowa, BS; Jed Bondy, BS; Caroline Aprigliano, BS; Peter B. White, DO, MS; Jonathan R. Danoff, MD (Arthroplasty Today)
Background: There is a paucity of validated risk stratification tools to assess which patients can safely and predictably undergo outpatient total hip (THA) or knee arthroplasty (TKA) in an ambulatory surgery center (ASC). Methods: Our novel patient selection tool was prospectively applied to 190 consecutive primary THA and TKA performed by a single surgeon at a single ASC. We identified the proportion of patients discharged home the same day, those requiring a one-night stay, or those with failed discharge within 23 hours. A retrospective chart review was performed to determine if any demographic parameters were risk factors for an overnight stay. Results: Overall, 190 (100%) patients selected for outpatient THA and TKA were discharged home within 23 hours. One hundred and four patients (55%) were discharged the same day of surgery, whereas 86 (45%) required overnight stay and were discharged on postoperative day 1. Female sex (odds ratio [OR]: 4.1, 95% confidence interval [CI]: 2.0-8.2, P < .001), THA (OR: 2.5, 95% CI: 1.1-5.5, P = .022), and heavier body mass index (OR: 1.0, 95% CI: 1.0-1.2, P = .022) were identified as independent risk factors for staying overnight in the ASC. Conclusions: In this pilot study, we found that 100% of outpatient THA and TKA-eligible patients were able to be discharged home by postoperative day 1. Additionally, we found that this selection tool is safe and effective at predicting short-stay discharge in an ASC.